EVALUATE THE SERVICE QUALITY OF SAM RATULANGI INTERNATIONAL AIRPORT USING IMPORTANCE AND PERFORMANCE ANALYSIS (IPA) - Simbar, Prasista Ekklesia; Massie, James D. D.; Tumewu, Ferdinand (Universitas Sam Ratulangi, 2016)
Abstract: Aviation is one of the most fundamental aspect that affect the global development significantly in the new century and it is considered as an important inputs into wider economic, political, and social processes. Lately, airport in Indonesia shows significantly improvement from their building until the service and noted there are three airport in Indonesia considered to be overcapacity. This fact indicating the economic in Indonesia grew rapidly by increasing the amount of visitor. To support air travel industry, airport needs to provide a good service quality and adequate facility in order to satisfy customer. This research aims to evaluate the service quality of Sam Ratulangi International Airport. The type of this research is a Quantitative Descriptive Research by using Importance and Performance Analysis (IPA). The sample of this research is 100 respondents who already experience the service quality of Sam Ratulangi International Airport. The sample was taken by simple random sampling. This research suggests that Sam Ratulangi International Airport needs to their performance in some attributes in order to satisfy the user.